2018
DOI: 10.1177/0091415018812404
|View full text |Cite
|
Sign up to set email alerts
|

Work and the Family in Later Life: The Effects of Role Stressors, Role Enhancement, and Role Conflict on Self-Perceptions on Aging

Abstract: The growing aging workforce comprises older workers with a concurrent family role. Guided by life span development and role theories, the primary study hypothesis was that rewards and stressors in the family and work domains would impact self-perceptions on aging because of the enhancement and conflict between these domains. The study sample consisted of workers older than 50 years with at least one of four family roles (spouse, parent of adult children, caregiver to an aging parent, and grandparent) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…One outstanding factor in this study was the relationship between role in the group and community commitment. Regarding roles, it has been reported that work and family roles are important to one's identity at older ages [ 58 ]. A previous study among older adults reported that taking on a leadership position in an organization can reduce the risk of dementia by approximately 20% in young-old people [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One outstanding factor in this study was the relationship between role in the group and community commitment. Regarding roles, it has been reported that work and family roles are important to one's identity at older ages [ 58 ]. A previous study among older adults reported that taking on a leadership position in an organization can reduce the risk of dementia by approximately 20% in young-old people [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CCS score was approximately 1.5 times higher for the total population and approximately 1.4 times higher for members who answered “yes” to perception of a role in the group. Whereas there are reports on the importance of a group role [ 58 , 59 ], there are others reports cautioning against making such roles too burdensome for participants [ 31 ]. Thus, to increase community commitment, apart from thinking of leaders as advanced resources for the community, it is important to appropriate their roles so that group participants can better recognize their own roles.…”
Section: Discussionmentioning
confidence: 99%
“…One of the outstanding factors in this study was the relationship between role in the group and community commitment. Regarding roles, it has been reported that work and family roles are important to one's identity at older ages [57]. A previous study among older adults reported that taking on a leadership position in an organization can reduce the risk of dementia by approximately 20% in young-old people [58].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CCS score was approximately 1.5 times higher for the total population and approximately 1.4 times higher for members who answered "yes" to perception of a role in the group. Whereas there are reports on the importance of a group role [57,58], there are others reports cautioning against making such roles too burdensome for participants [31]. Thus, to increase community commitment, apart from thinking of leaders as advanced resources for the community, it is important to appropriate their roles so that group participants can better recognize their own roles.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the role strain theory, multiple social roles can be a source of a role conflict because one may not have enough resources, such as time, to fulfil responsibilities related to all of them (Goode, 1960). If older adults have demanding obligations, which exceed their reserves of strength and physical capacity, they are forced to choose in which social activity they will engage (Quach, 2020). Because, it could be challenging to combine roles as employees and grandchild caregivers, a role conflict may exist between these tasks.…”
Section: Grandparents' Employment Status and Grandchild Carementioning
confidence: 99%